Evaluation of the effectiveness of clustering algorithm in retrieving Malay documents / Aminah Mahmood - Mahmood, Aminah (2004)
In recent years, we have witnessed a tremendous growth in the volume of text documents available on the Internet, digital libraries, new sources and company-wide intranets. This has led to an increased interest in developing methods that can help users to effectively navigate, summarize and organize this information with the ultimate goal of helping them to find what they are looking for. The main issue in this information age is the efficiency and effectiveness of the retrieval system that can be used by the information provider. A good retrieval system should provide tools to perform searching accurately based on user requirements. Cluster analysis is a technique for multivariate analysis that assigns items to automatically created group based on a calculation of the degrees of association between items and groups. In the information retrieval (IR) field, cluster analysis has been used to create groups of documents with the goal of improving the efficiency and effectiveness of retrieval, or to determine the structure of the literature of a field. The IR community has explored docimient clustering as an alternative method of organizing retrieval results, but clustering has yet to be deployed on the major search engines. This study has evaluated and identified the effectiveness of clustering algorithm in Malay document retrieval system using Hadith test collections, which consists of Hadith documents, relevant judgments and one set of queries. Three types of experiments are conducted. First experiment use exact match, which is no method, is applied. Second experiment use stenmiing method. Finally, the last experiment uses combination of stemming and clustering methods.